Comprehensive analysis of observed changes in pressure systems and their impact on climatic elements over Iraq (for selected climatic stations) - Hassan Ali Abdul Zahra ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The research aims to analyze the temporal and spatial changes in surface pressure systems, represented by atmospheric highs and lows at the 1000 millibar level, over Iraq. The study also examines how these changes impact climatic characteristics in the region, particularly temperature, relative humidity, and rainfall. Daily weather maps and data published online (at 1200 GMT) were analyzed from sources such as http://vortex.plymouth.edu/reanal and the NOAA website. The research" involved calculating the number of days each type of surface pressure system occurred across two climate cycles: the first from 1960 to 1970 and the second from 2010 to 2020. The analysis identified three main atmospheric highs affecting the study area: the Siberian, European, and subtropical high-pressure systems. Additionally, it recognized three depressions: the Indian, Sudanese, and Mediterranean depressions. The study revealed significant changes in the occurrence rates of surface high-pressure systems between the two" periods. The European and Siberian highs recorded lower rates in the second cycle compared to the first, while the subtropical high showed an increase in its" recurrence rate during the second cycle. This shift contributed to higher temperature averages and lower relative humidity in the latter period. Conversely, the Sudanese and Mediterranean depressions experienced lower recurrence rates in the second climate cycle, whereas the Indian seasonal depression recorded higher rates, with the highest annual rate observed at Basra Station due to its proximity to the centers of the Indian seasonal depression. This resulted in decreased rainfall, higher evaporation rates, and lower relative humidity across all study stations, highlighting the distinct climatic variations among the locations analyzed.DOI: https://doi.org/10.54633/2333-024-056-028